COLLABORATIVE LEARNING TECHNOLOGIES: EFFECTIVENESS OF WORKING WITH SMALL GROUPS IN HIGHER EDUCATION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article examines the strategic implementation of collaborative learning technologies within the higher education system, focusing on the dynamics of small group interaction. The study analyzes how structured peer-to-peer engagement facilitates cognitive development, enhances problem-solving capabilities, and fosters professional communication skills.